Kaum Awam Sebagai Pelayan Tuhan dan Implikasinya Bagi Pelayanan Gerejawi di Pedesaan - Rio Marbun; David Manete; Sudi Hutagalung (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2022)
The availability of servants of God in the city is much more adequate than that available in the country and not only in holistic quality but also in quantity. This non-ideal development cannot be separated from the fact that the complexity of urban life problems is indeed much more heterogeneous, compared to rural areas. Those who are called specifically as servants of God who carry out ecclesiastical ministry duties are one of the other parts of the body of Christ such as the laity. Both the clergy and the laity are representations of the Church as bringers of light into the world in a holistic and contextual manner, both in urban areas but also in rural areas. Therefore the attention of ecclesiastical ministry should not only be for urban but also rural in other words rural should not be ignored. At this time the church is faced with the challenge of the need for a resilience of congregational faith and an outreach challenge as is its missional call to reach out to its surroundings. In fact, in terms of quantity alone, there is a lack of resources of God's Servants. So the purpose of this study is to look at the causality of the lack of ministers of God in the presence of the opportunity for the preaching of the gospel to be relieved and the increase in the faith of the congregation in the relief. The variable of this study is the presence of ministers of God with opportunities for ecclesiastical ministry and Christian testimony for rural areas. The research method used is Qualitative Grounded. The results obtained from this study are that the ministry in the village has a shortage of God's servants so that lay congregations experience the silting of faith and the continued impact becomes unproductive both in quality growth which also has an impact on quantity. Another crucial issue related to the missionary vocation of the church is that the tribes that are still neglected in the region remain neglected. Therefore, through this study, the author proposes that the church reactivate a model of coaching for the laity based on ministry and evangelism